Leveraging human capital for product innovation: The mediating role of online presence among micro and small enterprises in a developing economy - Meilisa, Meilisa; Handra, Hefrizal; Rahman, Hafiz; Putra, Febriandi Prima (Edelweiss Applied Science and Technology, 2026)
This study investigates the role of human capital and online presence in driving product innovation among Micro and Small Enterprises (MSEs) in Pekanbaru City, Indonesia, a developing urban area with increasing digital adoption. Grounded in the Resource-Based View (RBV), the research explores how internal capabilities, particularly employee knowledge and skills, interact with digital resources to enhance innovation outcomes. A quantitative, cross-sectional design was employed using primary data collected via structured questionnaires distributed to MSE owners and managers across various processing sectors. Structural Equation Modeling (SEM-PLS) was used for data analysis. The findings reveal that human capital has a strong, positive influence on product innovation, while online presence also contributes positively, albeit to a lesser extent. Additionally, online presence partially mediates the relationship between human capital and innovation outcomes, indicating that digital tools enhance the transformation of internal competencies into market-relevant products. These results underscore the importance of integrating human resource development with digital strategies to boost innovation capacity in MSEs. This study contributes to the RBV literature by highlighting the complementary role of online presence in maximizing the value of human capital within innovation processes, particularly in developing country contexts.